SGK1 repression by WT1 may confer a survival advantage to leukemic cells under stress conditions - Rubio, Miguel A.; Cisa-Wieczorek, Sabina; Mozos, Ana; Castellet, Helena; Bussaglia, Elena; Carricondo, Maite; Hernández-Alvarez, María Isabel; Sierra, Jorge; Nomdedéu, Josep F. (Annals of hematology, 2025)
Increased WT1 mRNA levels are pervasive in acute myeloid leukemia (AML), and this marker has been used to assess the leukemic compartment size after chemotherapy or hematopoietic cell transplants. Little is known about the effects of WT1 on the leukemic cells and their targets. This work used data obtained from gene expression arrays performed on AML samples with high and low WT1 mRNA levels to pinpoint genes that WT1 can regulate. We singled out SGK1 , which showed an inverse correlation between its mRNA levels and WT1 in leukemic cell lines and AML samples. In cellular models, forced expression of WT1 reduced mRNA and protein levels of SGK1 . Furthermore, WT1 repressed the SGK1 promoter activity, and accordingly, WT1 knockdown showed an increased expression of SGK1 . We also detected an inverse correlation between WT1 and SGK1 during leukemic cell-line differentiation. WT1 genetic knockdown displayed decreased cell viability under nutrient deprivation. By contrast, SGK1 knockdown or pharmacologic inhibition increased resistance to apoptosis in response to serum starvation, acting on cell cycle progression. The effects of SGK1 targeting in hematologic conditions merit further investigation.